2015
DOI: 10.14740/cr398e
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Idiopathic Cardiomyopathy After Colon Clear

Abstract: BackgroundThe study aimed to illustrate the effect of colon clear on idiopathic myocardial dysfunction. Helicobacter pylori colonized the stomach since an immemorial time, as if both the stomach and the bacterium used to live together in peace harmless to each other. H. pylori could migrate or get forced to migrate to the colon; antibiotics are seldom effective against extra-gastric H. pylori strains. The association of H. pylori and some cardiovascular diseases like myocarditis and cardiomyopaty has been suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…In this study and other studies, the effect of three times dilution of the natural senna leaves extract and twenty times dilution of dietary white vinegar (acetic acid 6%) were found directly lethal to H. pylori culture media [8,9].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In this study and other studies, the effect of three times dilution of the natural senna leaves extract and twenty times dilution of dietary white vinegar (acetic acid 6%) were found directly lethal to H. pylori culture media [8,9].…”
Section: Discussionsupporting
confidence: 55%
“…Existence of colonic H. pylori strains was confirmed by H. pylori fecal antigen test [7]. Natural eradication of colonic H. pylori strains was employed for all patients using the natural senna leaves pure, while colon care/colon clear was maintained by vinegar therapy [8,9]. Confirmation of H. pylori eradication from the colon was done using H. pylori fecal antigen test [7].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of excess ammonia in the body is known toxic that could lead to adverse biological effects in the body among predisposed disadvantaged population. Ammonia is smooth muscle tonic and therefore; excess ammonia in the colon could be spastic causing multiple colonic spasms [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This suggestion is supported by the fact that the pathology of these conditions is in progress and treatment results are not satisfactory although hormonal reasons of the these conditions are rather constant, anti-inflammatory measures and antibiotics are aggressive and effective, decongestives are still useful, cytotoxic drugs became more decisive while obstetric trauma is becoming minimal due development of better obstetric skills. As long as Helicobacter pylori has been found associated with many medical challenges having different influence in these challenges and as colonic H. pylori strains were found essentially responsible for the worst conditions of pelvic congestion due to accumulation of profuse toxic amounts of ammonia unopposed or buffered by any acidity; H. pylori was considered as a possible underlying etiologic pathology in cases of female pelvic pathology in general and in ovarian cystic disease and endometriosis in particular; therefore, patients of this study were screened for existence of colonic H. pylori strains and eradication of these strains was done by employing the potent natural senna leaves purge [12,19]. Pelvic pathology has been widely studied in female sex; these studies have shown that pelvic congestion and venous stasis are responsible for the development of varices which account for the symptoms and sequels of most female pelvic pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Confirmation of H. pylori eradication was done after colon clear using H. pylori fecal antigen test. Revision of therapy, both colon clear and cupping, the following month was decided according to the response of patients [12,13].…”
Section: Methodsmentioning
confidence: 99%